1998
DOI: 10.1212/wnl.51.5.1270
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study of the incidence of sudden unexplained death in epilepsy

Abstract: The incidence of SUDEP in our study was 0.35 per 1,000 person-years. SUDEP was responsible for 1.7% of deaths in our cohort. SUDEP is a rare cause of death in the epilepsy population but exceeds the expected rate of sudden death in the general population by nearly 24 times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
250
4
26

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(292 citation statements)
references
References 13 publications
(1 reference statement)
8
250
4
26
Order By: Relevance
“…Since different definitions of SUDEP have been used, not all patients have a post-mortem examination, and case ascertainment methods and source populations have varied (Tomson et al 2005). The incidence of SUDEP has been estimated to be 3.5/1000 person-years in a lamotrigine clinical trial (Leestma et al 1997), 0.5-1.4/1000 person-years in people with treated epilepsy (Tennis et al 1995), 5.9/1000 person-years in outpatients with epilepsy at a tertiary referral centre (Nashef et al 1995), and 0.35/1000 personyears in a population-based study (Ficker et al 1998). The National General Practice Study of Epilepsy (NG-PSE), a community-based study in the United Kingdom, saw the first case of SUDEP after 11,000 person-years of follow-up (Lhatoo and Sander 2001), and the results of the Medical Research Council Antiepileptic Drug Withdrawal Study showed that SUDEP is a rare event among patients with epilepsy in remission (1991).…”
Section: General Aspectsmentioning
confidence: 99%
“…Since different definitions of SUDEP have been used, not all patients have a post-mortem examination, and case ascertainment methods and source populations have varied (Tomson et al 2005). The incidence of SUDEP has been estimated to be 3.5/1000 person-years in a lamotrigine clinical trial (Leestma et al 1997), 0.5-1.4/1000 person-years in people with treated epilepsy (Tennis et al 1995), 5.9/1000 person-years in outpatients with epilepsy at a tertiary referral centre (Nashef et al 1995), and 0.35/1000 personyears in a population-based study (Ficker et al 1998). The National General Practice Study of Epilepsy (NG-PSE), a community-based study in the United Kingdom, saw the first case of SUDEP after 11,000 person-years of follow-up (Lhatoo and Sander 2001), and the results of the Medical Research Council Antiepileptic Drug Withdrawal Study showed that SUDEP is a rare event among patients with epilepsy in remission (1991).…”
Section: General Aspectsmentioning
confidence: 99%
“…This finding is consistent with previous observations that only a small proportions (25%) of the deaths were witnessed ¹². In Ficker s study, 8 (88.8%) of the 9 SUDEP patients were found death at home and only 2 (22.2%) had a seizure witnessed before being found dead 14 . Nashef et al reported that among 14 young SUDEP patients, 11 (78.5%) were found dead at home ¹¹.…”
Section: Discussionmentioning
confidence: 96%
“…Ficker et al reported alcohol abuse in 3 patients (42.8%) out of 7 SUDEP cases 14 . Both alcohol excess and medication withdrawal can precipitate seizures, but may also predispose to autonomic instability thus increasing the risk of ictal death 5 .…”
Section: Discussionmentioning
confidence: 97%
“…Comparisons of incidence estimates for SUDEP are difficult, since different definitions of SUDEP have been used, not all patients have a postmortem examination, and case ascertainment methods and source populations have varied 15 . The incidence of SUDEP has been estimated to be 3.5/1000 person-years in a lamotrigine clinical trial 16 , 0.5-1.4/1000 person-years in people with treated epilepsy 17 , 5.9/1000 person-years in outpatients with epilepsy at a tertiary referral centre 18 and 0.35/1000 person-years in a population-based study 19 . The National General Practice Study of Epilepsy (NGPSE), a community-based study in the United Kingdom, saw the first case of SUDEP after 11,000 person-years of follow-up 20 , and the results of the Medical research Council Antiepileptic Drug withdrawal Study showed that SUDEP is a rare event among patients with epilepsy in remission 21 .…”
Section: Sudden Unexpected Death In Epilepsymentioning
confidence: 99%